Preparation method of ultrahigh-strength high-conductivity copper alloy plate strip for lead frame
Through solid solution strengthening of Co and Mg elements and multi-pass aging treatment, the problem of difficulty in synergistically improving the conductivity and strength of copper alloy plate strips for lead frames in the prior art is solved, and the preparation of ultra-high strength and high conductivity copper alloy plate strips is achieved, and the process is simple.
Patent Information
- Application Number
- CN202510108678.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to coordinately improve conductivity and strength in copper alloy plate strips for lead frames, and the preparation process is immature.
Through solid solution strengthening of Co and Mg elements, multiple aging treatment was used to explore the aging peak near the recrystallization temperature, solute atoms Co, Mg and Ni content in the Cu matrix were reduced to improve conductivity, and the dislocation pinning effect of the precipitated phase (Ni,Co)xSi was strengthened to improve strength.
The ultra-high-strength high-conducting copper alloy plate for the prepared lead frame has a tensile strength σb≥850Mpa, a conductivity ≥46% IACS, and a yield strength σ0.2≥750MPa. It has uniform chemical composition, excellent mechanical properties and conductive properties, and a simple preparation process.
Smart Images

Figure CN119876690A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper alloys, and in particular to a method for preparing an ultra-high-strength and high-conductivity copper alloy strip for a lead frame. Background Art
[0002] Lead frame material is one of the main materials for integrated circuit packaging. Its main functions are: supporting and fixing silicon chips, outputting chip information, and serving as the main channel for chip heat dissipation. This requires it to have high strength, high electrical conductivity and good thermal conductivity.
[0003] For example, Chinese patent CN104630671A discloses a heat treatment and processing technology for high-performance copper alloy strips for lead frames. The specific process flow is: power frequency induction semi-continuous casting → hot rolling to 14×400mm with two-roll hot press → water quenching → curling → milling surface 12.6mm → two-roll three-frame continuous rolling to 4.0mm → bell furnace annealing → four-roll cold rolling mill rolling to 0.2mm → through-type continuous annealing → four-roll cold rolling to 0.15mm; wherein, the power frequency induction semi-continuous casting adopts a single ingot 4-type heating in a walking furnace, the heating temperature is 850℃, and during water quenching, the strong water cooling chamber is set above the discharge roller; the first bell furnace annealing temperature is 500℃, and the annealing time is 6h; the second bell furnace annealing temperature is 480℃, and the annealing time is 6h. The high-performance copper alloy for lead frames prepared by this method has a tensile strength greater than 450MPa, a conductivity greater than 60-70%IACS, and stable quality, scientific and reasonable process, and high production efficiency.
[0004] Chinese patent CN105316520B discloses a method for preparing a Cu-Ni-Sn copper alloy strip. By adjusting the chemical composition of Ni and Sn elements and improving the melting and casting process, the melting and casting quality is improved and defects such as pores and looseness of the product are reduced. The production process adopts a cold rolling process to improve the strength and an annealing process to eliminate work hardening. The ideal high-strength and high-elasticity Cu-Ni-Sn copper alloy material properties are obtained through the final cold working and stress relief methods.
[0005] Chinese patent CN111485132B discloses a copper alloy strip with excellent comprehensive performance and a preparation method thereof. The method dissolves Ni, Co and Si atoms into a copper matrix by high-temperature solid solution treatment, then forms a supersaturated solid solution by quenching treatment, and subsequently precipitates Ni by aging treatment. x Si y With Co x Si yThe precipitated phase plays a role of dispersion strengthening, thereby improving the tensile strength, yield strength and elastic modulus of the copper alloy strip. Ag is the main additive element, and Ag atoms exist in the copper alloy in the form of substitutional solid solution, providing an initial texture basis for forming a specific texture and area ratio in the copper alloy strip. In addition to playing a role of solid solution strengthening in the present invention, Ag atoms can improve the high temperature softening resistance and stress relaxation resistance of the copper alloy strip of the present invention, thereby achieving excellent comprehensive performance.
[0006] However, the conductivity and strength of the copper alloy strips for lead frames prepared by the prior art cannot be improved synergistically, and the strip assembly process is immature. Summary of the invention
[0007] In view of this, the present invention provides a method for preparing an ultra-high-strength and high-conductivity copper alloy plate and strip for a lead frame, which reduces the final aging temperature through the coupling mechanism of solid solution strengthening and precipitation strengthening of Co and Mg elements, achieves low carbon and energy saving, and the prepared strip has uniform chemical composition, excellent mechanical properties and conductive properties, and a simple preparation process.
[0008] The method for preparing the ultra-high-strength and high-conductivity copper alloy strip for the lead frame of the present invention comprises the following steps:
[0009] (1) Ingredients: weigh raw materials Ni, Si, Mg, Co, and Cu; the Cu includes copper tubes and other copper raw materials; the other copper raw materials are copper raw materials commonly used in the art, including but not limited to copper powder and copper ingots;
[0010] (2) Smelting: Mg is sealed in a copper tube, Ni, Si, Co and the remainder of Cu are added into a vacuum induction furnace, heated to melt in a protective atmosphere to obtain a melt, and the copper tube sealing Mg is immersed under the liquid surface of the melt to keep the temperature, and then cast and cool to obtain an ingot;
[0011] (3) solid solution: the ingot obtained in step (2) is subjected to surface milling treatment, and then placed in a muffle furnace for heating and heat preservation, and then the ingot is taken out and water-cooled;
[0012] (4) Hot rolling: The solution-cast ingot is heated and kept warm, and then hot rolled to obtain a slab;
[0013] (5) Cold rolling: cold rolling the slab in step (4) to obtain a plate with a thickness of 1-4 mm;
[0014] (6) Annealing: annealing the plate in step (5) at 400-450° C. for 3-5 h;
[0015] (7) Cold rolling again: The annealed sheet is cold rolled at a speed of 8-12% per pass to obtain a copper alloy sheet with a thickness of 0.1-0.4 mm. During the cold rolling process, any edge cracks that may occur are promptly removed;
[0016] (8) Final aging: The strip described in step (7) is annealed at 300-350° C. for 2-6 h to obtain an ultra-high strength and high conductivity copper alloy strip for lead frame.
[0017] Preferably, the mass percentages of the raw materials in step (1) are: Ni 0.8-2.0%, Si 0.2-1.2%, Mg 0.05-0.3%, Co 0.5-2.5%, and the balance is Cu.
[0018] Preferably, the specific steps of heating in step (2) are: first, evacuate the vacuum induction furnace to below 15Pa, and introduce a protective atmosphere to 0.04-0.05Mpa; then start heating, and stop heating when all the solids are melted and the temperature rises to 1400-1500°C.
[0019] More preferably, the protective atmosphere is argon.
[0020] Preferably, the insulation time in step (2) is 30s-2min.
[0021] Preferably, the cooling time in step (2) is 20-40 minutes.
[0022] Preferably, the heating rate in step (3) is 5-7°C / min; the heating temperature is 800-900°C; and the insulation time is 3-5h.
[0023] Preferably, the heating temperature in step (4) is 700-800° C., and the insulation time is 15-40 min.
[0024] Preferably, the hot rolling in step (4) is performed by multiple passes, with the pressing amount in each pass being 15-30%, and the final rolling amount being 40-50%.
[0025] Preferably, the cold rolling in step (5) is performed by multiple passes, with the pressing amount in each pass being 8-12%.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention provides a method for preparing an ultra-high strength and high conductivity copper alloy strip for lead frames, which comprises the following steps in sequence: first, Mg is sealed in a copper tube, then added below the melt level of Cu, Ni, Si, and Co, and subjected to solution treatment, hot rolling, cold rolling, annealing, and cold rolling again to obtain an ultra-high strength and high conductivity copper alloy strip for lead frames. The present invention adopts multiple aging processes, explores the aging peak near the recrystallization temperature, reduces the content of solute atoms Co, Mg, and Ni in the Cu matrix to improve conductivity, and strengthens the precipitated phase (Ni, Co). x The dislocation pinning effect of Si improves the strength, and this composite strengthening mechanism dominates the synergistic optimization and improvement of the key properties of the alloy strip.
[0028] The tensile strength of the strip prepared by the present invention is b ≥850Mpa, conductivity ≥46%IACS, yield strength σ 0.2 ≥750MPa, the strip has uniform chemical composition, excellent mechanical properties and electrical conductivity, and simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a metallographic diagram of the ingot obtained by solution treatment in Example 1;
[0030] Figure 2 The metallographic image of the ultra-high strength and high conductivity copper alloy strip for the lead frame prepared in Example 1;
[0031] Figure 3 This is the metallographic image of the ingot obtained by solution treatment in Comparative Example 1;
[0032] Figure 4 This is a metallographic image of the copper alloy strip for lead frame prepared in Comparative Example 1. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Example 1
[0035] A method for preparing an ultra-high-strength and high-conductivity copper alloy strip for a lead frame, comprising the following steps:
[0036] (1) Ingredients: Weigh 1000 g of raw materials according to the following mass percentages: Ni = 1.6%; Si = 0.8%; Mg = 0.1%; Co = 1.0%, and the balance is Cu; the Cu includes pure copper tubes and other copper raw materials;
[0037] (2) Melting: Mg is sealed in a pure copper tube and fixed on the robot arm of a vacuum induction furnace, and Cu (minus the mass of the pure copper tube), Ni, Si, and Co are added to the crucible of the vacuum induction furnace; the vacuum induction furnace is evacuated to below 15 Pa, and a protective atmosphere of argon gas is introduced to 0.05 MPa, and then an induction power supply is introduced to start heating. When all the solids in the crucible are melted and the temperature rises to 1400°C, the induction current is turned off, and the robot arm is quickly operated to immerse the pure copper tube sealing Mg under the melt surface, and the induction current is turned on to continue to keep the temperature for 1 minute. After the temperature is kept, casting is carried out. After the casting is completed, it is cooled for 30 minutes and taken out to obtain an ingot;
[0038] (3) Solution treatment: The ingot is milled and then placed in a muffle furnace and heated to 850°C at a heating rate of 5°C / min for 4 hours. After the heating is completed, the ingot is taken out and water-cooled. The metallographic image of the ingot is as follows: Figure 1 ;
[0039] (4) Hot rolling: the solution-treated ingot is placed in a muffle furnace at 750°C for 30 min, taken out and sent to a hot rolling mill for a rolling process with a reduction of 20% per pass and a final rolling reduction of 50% to obtain a slab;
[0040] (5) Cold rolling: The slab is fed into a cold rolling mill and cold rolled at a rate of 10% per pass to obtain a plate with a thickness of 2 mm;
[0041] (6) Annealing: The plate was annealed at 430 °C for 4 h;
[0042] (7) Cold rolling again: The annealed sheet is cold rolled at a rate of 10% reduction per pass to obtain a copper alloy sheet with a thickness of 0.2 mm (the edge cracks that may appear are removed in time during the cold rolling process);
[0043] (8) Final aging: The strip of step (7) is annealed at 320° C. for 2 h to obtain an ultra-high strength and high conductivity copper alloy strip for lead frame. The metallographic structure of the ultra-high strength and high conductivity copper alloy strip for lead frame is as follows: Figure 2 .
[0044] Performance tests were conducted on the ultra-high strength and high conductivity copper alloy strip used for the lead frame, and the results showed that the hardness of the strip was HV = 289.2, the tensile strength σb = 874.5 MPa, the conductivity = 47.5% IACS, and the yield strength σ0.2 = 764 MPa.
[0045] Example 2
[0046] A method for preparing an ultra-high-strength and high-conductivity copper alloy strip for a lead frame, comprising the following steps:
[0047] (1) Ingredients: Weigh 1000 g of raw materials according to the following mass percentages: Ni = 1.4%; Si = 0.7%; Mg = 0.1%; Co = 1.0%, and the balance is Cu; the Cu includes pure copper tubes and other copper raw materials;
[0048] (2) Melting: Mg is sealed in a pure copper tube and fixed on the robot arm of a vacuum induction furnace, and Cu (minus the mass of the pure copper tube), Ni, Si, and Co are added to the crucible of the vacuum induction furnace; the vacuum induction furnace is evacuated to below 15 Pa, and a protective atmosphere of argon gas is introduced to 0.05 MPa, and then an induction power supply is introduced to start heating. When all the solids in the crucible are melted and the temperature rises to 1400°C, the induction current is turned off, and the robot arm is quickly operated to immerse the pure copper tube sealing Mg under the melt surface, and the induction current is turned on to continue to keep the temperature for 2 minutes. After the temperature is kept, casting is carried out. After the casting is completed, it is cooled for 30 minutes and taken out to obtain an ingot;
[0049] (3) Solid solution: The ingot is milled and then placed in a muffle furnace and heated to 800°C at a heating rate of 5°C / min for 5 h. After the insulation is completed, the ingot is taken out and water-cooled;
[0050] (4) Hot rolling: the solution-treated ingot is placed in a muffle furnace at 700°C for 40 min, taken out and sent to a hot rolling mill for a rolling process with a reduction of 20% per pass and a final rolling reduction of 50% to obtain a slab;
[0051] (5) Cold rolling: The slab is fed into a cold rolling mill and cold rolled at a rate of 10% per pass to obtain a plate with a thickness of 2 mm;
[0052] (6) Annealing: anneal the plate at 400°C for 5 h;
[0053] (7) Cold rolling again: The annealed sheet is cold rolled at a rate of 10% reduction per pass to obtain a copper alloy sheet with a thickness of 0.2 mm (the edge cracks that may appear are removed in time during the cold rolling process);
[0054] (8) Final aging: The strip described in step (7) is annealed at 350° C. for 2 h to obtain an ultra-high strength and high conductivity copper alloy strip for lead frame.
[0055] Performance tests were conducted on the ultra-high strength and high conductivity copper alloy strip used for the lead frame, and the results showed that the hardness of the strip was HV = 281.9, the tensile strength σb = 863.7 MPa, the conductivity = 49.4% IACS, and the yield strength σ0.2 = 762.4 MPa.
[0056] Example 3
[0057] A method for preparing an ultra-high-strength and high-conductivity copper alloy strip for a lead frame, comprising the following steps:
[0058] (1) Ingredients: Weigh 1000 g of raw materials according to the following mass percentages: Ni = 1.9%; Si = 0.6%; Mg = 0.08%; Co = 1.0%, and the balance is Cu; the Cu includes pure copper tubes and other copper raw materials;
[0059] (2) Melting: Mg is sealed in a pure copper tube and fixed on the robot arm of a vacuum induction furnace, and Cu (minus the mass of the pure copper tube), Ni, Si, and Co are added to the crucible of the vacuum induction furnace; the vacuum induction furnace is evacuated to below 15 Pa, and a protective atmosphere of argon gas is introduced to 0.05 MPa, and then an induction power supply is introduced to start heating. When all the solids in the crucible are melted and the temperature rises to 1500° C., the induction current is turned off, and the robot arm is quickly operated to immerse the pure copper tube sealing Mg under the melt surface, and the induction current is turned on to continue to keep the temperature for 2 minutes. After the temperature is kept, casting is carried out. After the casting is completed, it is cooled for 30 minutes and taken out to obtain an ingot;
[0060] (3) Solution treatment: The ingot is milled and then placed in a muffle furnace and heated to 900°C at a heating rate of 5°C / min for 3 h. After the insulation is completed, the ingot is taken out and water-cooled;
[0061] (4) Hot rolling: the solution-treated ingot is placed in a muffle furnace at 800°C for 15 min, taken out and sent to a hot rolling mill for a rolling process with a reduction of 30% per pass and a final rolling reduction of 50% to obtain a slab;
[0062] (5) Cold rolling: The slab is fed into a cold rolling mill and cold rolled at a rate of 10% per pass to obtain a plate with a thickness of 2 mm;
[0063] (6) Annealing: anneal the plate at 500 °C for 3 h;
[0064] (7) Cold rolling again: The annealed sheet is cold rolled at a rate of 10% reduction per pass to obtain a copper alloy sheet with a thickness of 0.2 mm (the edge cracks that may appear are removed in time during the cold rolling process);
[0065] (8) Final aging: The strip described in step (7) is annealed at 300° C. for 3 h to obtain an ultra-high strength and high conductivity copper alloy strip for lead frame.
[0066] Performance tests were conducted on the ultra-high strength and high conductivity copper alloy strip used for the lead frame, and the results showed that the hardness of the strip was HV = 285.6, the tensile strength σb = 877.4 MPa, the conductivity = 46.3% IACS, and the yield strength σ0.2 = 769.8 MPa.
[0067] Comparative Example 1
[0068] A method for preparing a copper alloy strip for a lead frame, comprising the following steps:
[0069] (1) Ingredients: 1000 g of raw materials are weighed according to the following mass percentages: Ni = 1.9; Si = 0.6; the balance is Cu; the Cu includes pure copper tubes and other copper raw materials;
[0070] (2) Melting: Add Cu, Ni and Si into a crucible of a vacuum induction furnace; evacuate the vacuum induction furnace to below 15 Pa, introduce protective argon gas to 0.05 MPa, and then introduce an induction power supply to start heating. When all the solids in the crucible are melted and the temperature rises to 1500°C, turn off the induction current, and quickly cast. After the casting is completed, cool for 30 minutes and take out the ingot;
[0071] (3) Solution treatment: The ingot is milled and then placed in a muffle furnace and heated to 900°C at a heating rate of 5°C / min for 3 hours. After the heating is completed, the ingot is taken out and water-cooled. The metallographic image of the ingot is obtained as shown in FIG. Figure 3 ;
[0072] (4) Cold rolling: The solutionized ingot is sent to a cold rolling mill and cold rolled at a rate of 10% per pass to obtain a copper alloy strip with a thickness of 0.2 mm (the edge cracks that may appear are removed in time during the cold rolling process);
[0073] (5) Final aging: The strip of the step (4) is subjected to annealing treatment at 320° C. for 4 h to obtain a copper alloy strip for a lead frame; the metallographic structure of the copper alloy strip for a lead frame is as follows: Figure 4 .
[0074] Performance tests on the copper alloy strip for lead frame showed that the strip had a hardness of HV = 187.6, a tensile strength σb = 540.3 MPa, a conductivity = 40.1% IACS, and a yield strength σ0.2 = 510.6 MPa.
[0075] from Figure 1 to Figure 4 It can be seen that the grains of the ultra-high strength and high conductivity copper alloy strip used for the lead frame in Example 1 are significantly finer than those in Comparative Example 1.
[0076] It can be seen that after the addition of Co, the cast grains become finer, and more precipitates are formed at the grain boundaries, which promotes grain refinement by providing heterogeneous nucleation points; the (Ni, Si) precipitates (gray particles in the figure) in the strip are more evenly distributed and have a finer morphology, and the copper matrix is purer, which reduces the scattering effect of defects on electrons and helps to improve the conductivity of the strip.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an ultra-high strength and high conductivity copper alloy strip for a lead frame, characterized in that: The following steps are involved: (1) Ingredients: weigh raw materials Ni, Si, Mg, Co, and Cu; the Cu includes copper tubes and other copper raw materials; (2) Smelting: Mg is sealed in a copper tube, Ni, Si, Co and the remainder of Cu are added into a vacuum induction furnace, heated to melt in a protective atmosphere to obtain a melt, and the copper tube sealing Mg is immersed under the liquid surface of the melt to keep the temperature, and then cast and cool to obtain an ingot; (3) solid solution: the ingot obtained in step (2) is subjected to surface milling treatment, and then placed in a muffle furnace for heating and heat preservation, and then the ingot is taken out and water-cooled; (4) Hot rolling: The solution-cast ingot is heated and kept warm, and then hot rolled to obtain a slab; (5) Cold rolling: cold rolling the slab in step (4) to obtain a plate with a thickness of 1-4 mm; (6) Annealing: annealing the plate in step (5) at 400-450° C. for 3-5 h; (7) Cold rolling again: cold rolling the annealed sheet at a rate of 8-12% per pass to obtain a copper alloy sheet with a thickness of 0.1-0.4 mm; (8) Final aging: The strip described in step (7) is annealed at 300-350° C. for 2-6 h to obtain an ultra-high strength and high conductivity copper alloy strip for lead frame.
2. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The mass percentages of the raw materials in step (1) are: Ni 0.8-2.0%, Si 0.2-1.2%, Mg 0.05-0.3%, Co 0.5-2.5%, and the balance is Cu.
3. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The specific steps of heating in step (2) are: first, evacuate the vacuum induction furnace to below 15Pa, introduce a protective atmosphere to 0.04-0.05Mpa; then start heating, and stop heating when all the solids are melted and the temperature rises to 1400-1500°C.
4. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 3, characterized in that: The protective atmosphere is argon.
5. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The insulation time of step (2) is 30s-2min.
6. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The cooling time in step (2) is 20-40 minutes.
7. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The heating rate of step (3) is 5-7°C / min; the heating temperature is 800-900°C; and the insulation time is 3-5h.
8. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The heating temperature in step (4) is 700-800° C. and the insulation time is 15-40 minutes.
9. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The hot rolling in step (4) is performed by multiple passes, with each pass reducing by 15-30% and the final rolling reducing by 40-50%.
10. The method for preparing the ultra-high strength and high conductivity copper alloy strip for lead frame according to claim 1, characterized in that: The cold rolling in step (5) is performed by multiple passes, with the pressing amount in each pass being 8-12%.
Citation Information
Patent Citations
Heat treatment and processing technology of high performance copper alloy plate for lead frame
CN104630671A
A method for preparing Cu-Ni-Sn copper alloy strip
CN105316520B
A copper alloy strip with excellent comprehensive performance and its preparation method
CN111485132B